Adaptação cultural do special needs kids questionnaire (SpeNK-Q) para o português do Brasil - Ferreira, Larissa Tassim Luciano (Universidade Federal de São Carlos, 2020)
Introduction: premature newborns discharged from neonatal intensive care normally face numerous challenges for care provision and constitute children with special health needs. After hospital discharge, the challenge of continuity of care arises given the need for multidisciplinary health follow-up. Objective: to perform the cultural adaptation of the Special Needs Kids Questionnarie to Brazilian Portuguese. Method: methodological study that covered the following steps: translation, back-translation, content validation and semantic validation. After translation and back-translation, the translated version underwent content validation. Four criteria were adopted for content validation: conceptual equivalence, item equivalence, operational equivalence and semantic equivalence. A Likert scale was used with the answers: I disagree, undecided and I agree. For analysis, the Content Validation Index was calculated, and a value equal to or greater than 0.80 was considered valid. In the step of semantic validation, mothers of premature newborns discharged from a Neonatal Intensive Care Unit performed a general analysis of the instrument and a specific analysis of its items. The interviews were audio-recorded and later transcribed. The ethical principles of research involving human beings were followed. Result: an expert committee composed of ten neonatal and pediatric nursing professionals with academic and/or clinical experience participated in the content validation step. The Content Validation Index for the criterion “semantic equivalence” was less than 0.80 in ten items, which were reviewed until the experts reached a consensus. The new version developed was analyzed by 24 mothers, out of which 12 had high school education and 12 had higher education. Most mothers (88%) evaluated the instrument positively, 16 (66%) indicated that all questions were easy, 21 (88%) said they had no difficulty with the answer categories and 23 (96%) considered the instrument very relevant. In the specific analysis, there was no difference in the distribution of responses regarding the attributed difficulty and the correct explanation of items between mothers with high school and those with higher education; 75% of items were correctly understood by mothers. Items related to the practice of home visits were considered “not important” among mothers with higher education. Conclusion: in the opinion of experts, the adapted version demonstrated content validity and was considered understandable by mothers. The use of this instrument by nursing is recommended as a support to their practice.
Cultural adaptation of the special needs kids questionnaire (SpeNK-Q) to brazilian portuguese
Keywords: Recém nascido prematuro; Continuidade da assistência ao paciente; Enfermagem; Premature newborn; Continuity of patient care; Nursing; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM PEDIATRICA